Why we should not routinely apply irreversible electroporation as an alternative curative treatment modality for localized prostate cancer at this stage - Wendler, Johann J.; Ganzer, Roman; Hadaschik, Boris; Blana, Andreas; Henkel, Thomas; Köhrmann, Kai-Uwe; Machtens, Stefan; Roosen, Alexander; Salomon, Georg; Sentker, Ludger Josef; Witzsch, Ulrich; Schlemmer, Heinz-Peter; et al. (World journal of urology, 2017)
Irreversible electroporation (IRE), a new tissue ablation procedure available since 2007, could meet the requirements for ideal focal therapy of prostate cancer with its postulated features, especially the absence of a thermal ablation effect. Thus far, there is not enough evidence of its effectiveness or adverse effects to justify its use as a definitive treatment option for localized prostate cancer. Moreover, neither optimal nor individual treatment parameters nor uniform endpoints have been defined thus far. No advantages over established treatment procedures have as yet been demonstrated. Nevertheless, IRE is now being increasingly applied for primary prostate cancer therapy outside clinical trials, not least through active advertising in the lay press. This review reflects the previous relevant literature on IRE of the prostate or prostate cancer and shows why we should not adopt IRE as a routine treatment modality at this stage.
First online: 04 May 2016
Gesehen am 26.11.2018